1997
DOI: 10.1038/385537a0
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-ligand binding properties govern cell migration speed through cell-substratum adhesiveness

Abstract: Migration of cells in higher organisms is mediated by adhesion receptors, such as integrins, that link the cell to extracellular-matrix ligands, transmitting forces and signals necessary for locomotion. Whether cells will migrate or not on a given substratum, and also their speed, depends on several variables related to integrin-ligand interactions, including ligand levels, integrin levels, and integrin-ligand binding affinities. These and other factors affect the way molecular systems integrate to effect and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

103
997
6
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,303 publications
(1,109 citation statements)
references
References 28 publications
103
997
6
3
Order By: Relevance
“…In contrast to the results of adhesion and spreading assay, of all the CHO cells investigated, CHO-K1 cells with the native level of a5 migrated most effectively to fibronectin ( Figure 4C). These data are consistent with the theory that cell migration is controlled by dynamic interactions between cell receptors and substratum ligands in a manner representing events at the front and rear of the migrating cells (Palecek et al, 1996(Palecek et al, , 1997Regen and Horwitz, 1992). The rate of kidney metastasis appears to shift in parallel with the adhesion of CHO cells to fibronectin, except for a5CHO cells that do not develop a primary site.…”
Section: Adhesion and Migration Of Cho Cells To Fibronectin In Vitrosupporting
confidence: 88%
“…In contrast to the results of adhesion and spreading assay, of all the CHO cells investigated, CHO-K1 cells with the native level of a5 migrated most effectively to fibronectin ( Figure 4C). These data are consistent with the theory that cell migration is controlled by dynamic interactions between cell receptors and substratum ligands in a manner representing events at the front and rear of the migrating cells (Palecek et al, 1996(Palecek et al, , 1997Regen and Horwitz, 1992). The rate of kidney metastasis appears to shift in parallel with the adhesion of CHO cells to fibronectin, except for a5CHO cells that do not develop a primary site.…”
Section: Adhesion and Migration Of Cho Cells To Fibronectin In Vitrosupporting
confidence: 88%
“…After this is the detachment to the substrate at the rear of the cell, allowing tail retraction and forward translocation of the cell body [20,21]. The ability to spread and subsequently migrate depends on a critical value of adhesive strength between cell and substrate: high or low levels of substrate attachment inhibit spreading and migration, whereas maximum migration occurs at intermediate adhesion strengths [22]. We found that SMC transfected by VCAM-1 siRNA displayed significant inhibition in migration compared to the cells transfected with control siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with cultured cells have shown a close correlation between cell-substratum adhesive strength and migration rates [131]. Evidence for a role of syndecans in modulating cell-migration activity comes from studies of lymphocyte migration.…”
Section: Cell Migrationmentioning
confidence: 99%